2005
DOI: 10.1002/art.21584
|View full text |Cite
|
Sign up to set email alerts
|

Pain as a mediator of sleep problems in arthritis and other chronic conditions

Abstract: Objective. To examine the associations between arthritis and insomnia symptoms and unrefreshing sleep, as well as the role of pain as a mediator of these relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
98
2
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 35 publications
13
98
2
3
Order By: Relevance
“…On the contrary, the presence of nocturnal knee pain is an important factor in the clinical evaluation of OA severity and outcomes after treatment. Reports have shown a wide range in the prevalence of nocturnal pain, from 17.6 -81.0% (3)(4)(5)(6). This wide range is likely because of different diagnostic methods, such as by questionnaire only or by examining past history of treatment for arthritis, including hip and knee OA, rheumatoid arthritis, and osteonecrosis (ON).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the presence of nocturnal knee pain is an important factor in the clinical evaluation of OA severity and outcomes after treatment. Reports have shown a wide range in the prevalence of nocturnal pain, from 17.6 -81.0% (3)(4)(5)(6). This wide range is likely because of different diagnostic methods, such as by questionnaire only or by examining past history of treatment for arthritis, including hip and knee OA, rheumatoid arthritis, and osteonecrosis (ON).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, sleep disturbances have been associated with common medical illnesses, including cerebrovascular and coronary artery disease (31). Perception of pain is believed to have a significant effect on sleep disturbance in patients with arthritis and other general medical conditions (32).…”
mentioning
confidence: 99%
“…14 Another factor related to the presence of chronic pain is insomnia and unrefreshing sleep, which tend to worsen as the level of pain increases. 19,25 Since the elders of our study have shown a low pain level, it was expected to observe a better sleep quality, and in fact they did not complain of sleep problems.…”
Section: Discussionmentioning
confidence: 86%